Financial Technology, Financial Literacy, and MSMEs' Financial Performance: The Mediating Role of Financial Inclusion in East Java - Setiyawan, Raymond; Tambunan, Damelina Basauli (Universitas Ciputra Surabaya, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are key contributors to economic growth, yet many still experience constraints in accessing formal financial systems. This research analyzes the impact of financial technology and financial literacy on the financial performance of MSMEs, while considering financial inclusion as an intervening variable. The study adopts a quantitative design using primary data collected through questionnaires from 160 MSMEs owners who actively use digital financial services. The data were processed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The findings reveal that financial literacy significantly enhances both financial inclusion and MSMEs financial performance. Furthermore, financial inclusion plays a mediating role in the relationship between financial literacy and financial performance. In contrast, financial technology does not demonstrate a significant direct influence on MSMEs financial performance, nor does financial inclusion mediate this relationship. The results emphasize the critical role of improving financial literacy in conjunction with expanding access to digital financial services to support better financial outcomes for MSMEs.